Modified thermal balloon endometrial ablation for treatment of heavy menstrual bleeding - Baraa Lukman Humo Al-Ibrahim; Ahmed Jasim Al Husaynei (Gynecology and Minimally Invasive Therapy, 2022)
Objectives: The objective of this study was to determine the efficacy of modified thermal balloon ablation using Foley's catheter in the treatment of heavy menstrual bleeding (HMB). Materials and Methods: Twelve patients with HMB aged 35–55 years underwent modified thermal balloon ablation using Foley's catheter. Patients were selected after complete clinical evaluation and investigations. The procedure was undertaken in the operation theater under general anesthesia/intravenous sedation. Three cycles of modified thermal balloon ablation using Foley's catheter were performed to ablate the endometrium. The time given to each cycle was 7 min. All the cycles were performed in the same setting. The main outcome measures that were studied were reduction in the menstrual flow, the need for further treatment, and relief of dysmenorrhea if present. Outcome measure regarding reduction in menstrual flow was statistically analyzed using Fisher's exact test. Statistical significance was determined at a level of P < 0.05. Results: Eighty-two percent of patients experienced a reasonable reduction in menstrual blood flow at 3-month follow-up. Eighteen percent observed no change in bleeding pattern and needed further treatment after failure of the procedure. Forty-two percent of patients complained of minor side effects such as cramp lower abdominal pain and fever. Rupture of balloon during the procedure occurred in only one case (8%). Conclusion: Modified thermal balloon ablation with Foley's catheter can be a promising management of HMB in resource-poor settings. It is a cost-effective alternative to the original endometrial ablation techniques.